Residents’ perception of their quality of life in TTDI area of Kuala Lumpur city, Malaysia - Mohit, Mohammad Abdul; Hj. Mohd. Noor, Norzailawati; Zahari, Rustam Khairi; Abdul Malek, Nurhayati; Johari Ramzan, Nadiah (2016)
This paper investigates the quality of life at a neighborhood level within seven domains that is the key determinant of the overall quality of life of Kuala Lumpur City. 260 sample residents belonging to eight types of housing of TTDI area were selected for questionnaire survey. The findings show that the residents are not satisfied with their economic condition and the safety condition that prevail in the area while they are a little over slightly satisfied concerning their housing condition, functional environment, and social and community participation. Concerning spiritual life residents are nearly satisfied,however, with the physical and emotional health condition, residents appear to be moderately satisfied. Regression analysis shows that residents’ overall assessment of QOL is determined by five components – satisfactions with spiritual life, functional environment, social and community participation,physical and emotional health and housing condition. The paper suggests that the indicators of the five components in which residents have expressed their non-satisfaction should be improved to enhance the quality of life of TTDI residents.